ANALISIS KEBIJAKAN DPPAI UII DALAM PENGUATAN NILAI KEAGAMAAN MAHASISWA BARU - Al Khurriyyah, Liza Jauharotul Munfarida; Ginanjar Firdaus, Rizky (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to analyze the policies of the Directorate of Islamic Education and Development (DPPAI) at Universitas Islam Indonesia (UII) in strengthening the religious values of new students. These policies are implemented through programs such as the Orientation of Basic Islamic Values (ONDI), Basic Islamic Values Pesantren (PNDI), Leadership and Da'wah Training (PKD), as well as Personal Development Training (PPD), which aim to shape students' character in accordance with Islamic values. The research methods include document analysis, interviews, and participatory observation to evaluate the effectiveness of these policies and programs. The findings indicate that these policies have successfully enhanced students' understanding of religion and encouraged them to actively participate in religious activities. Supporting factors for success include the quality of educators, student engagement, continuous evaluation, and support from the university and community. These policies have created a positive impact on shaping students' character to be religious, tolerant, and contributive to society. With ongoing evaluation and adaptation, DPPAI programs are expected to address contemporary challenges and produce a young generation with integrity and leadership rooted in Islamic values.